Service Quality, Satisfaction, and Loyalty of BNI Mobile Banking E-Customer - Brigitta Heidy; Kurniawati; Anniza Bellarisi Cantika; Faadiyah Nisa; Miranti Anggorodhiyu Lokantari (Business and Entrepreneurial Review, 2022)
Many banks institution have implemented mobile banking as a successful e-commerce application to give the combined benefits of increased customer service and cost reduction. Service quality is a comprehensive customer evaluation of a particular service and meets customer expectations and provides satisfaction. Objective: to assess whether service quality has a strong association to customers loyalty of BNI mobile banking users of FKG USAKTI professional students. Method: The data analyzed comes from BNI M-banking consumers, FKG professional students, who have been using BNI m-banking for a long time. The number of samples is about 150 people. Descriptive data analysis presented each item of the research questionnaire. Result: user friendliness and efficiency are determined to have a positive and considerable impact on customer satisfaction, whereas customer satisfaction has a significant and positive impact on customer loyalty.